MICELLAR MICROPARTICLES: A NOVEL APPROACH TO TOPICAL DRUG DELIVERY SYSTEM - Bansal, Monisha; Jamil, Shahid (International Journal of Applied Pharmaceutics, 2018)
Topical drug delivery system is defined as the pharmaceutical dosage form which when applied onto the skin provides protection of skin and prevents serious skin disorders. Topical drug are being used for several years and still have its potential in new pharmaceutical technologies investigated. Skin is the most easily accessible organ of the body which has the potential to facilitate the delivery of several drugs with better efficacy, confining the pharmacological or other effect of the drug to the surface of the skin. Micelles are colloidal particles with a size smaller than 100 nm that allow a great depth of tissue penetration for targeted drug delivery, but rapidly disintegrate in the body. Microparticles containing micelles have the potential for delivering hydrophobic drug encapsulated in micelles on the target site in the specific part of the body. Micellar microparticles allow the improvement of solubility and dissolution of poorly soluble drugs. Microparticles containing micelles have the potential for delivering micelle-encapsulated hydrophobic drugs in targeted therapy. This article reviews the topical drug delivery system, colloidal drug delivery system and aspects and literature reviewed on micellar microparticles and its advantages in pharmaceuticals. An overview of reviews was conducted to locate published literature between 2000 and 2017.Â 